2009
DOI: 10.1080/00480169.2009.36885
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of electroencephalographic responses to slaughter by non-penetrative captive-bolt stunning after ventral-neck incision in halothane-anaesthetised calves

Abstract: Non-penetrative captive-bolt stunning after ventral-neck incision resulted in the cessation of functional cortical activity in the majority of calves. This procedure prevented the development of cerebrocortical responses to ventral-neck incision, demonstrated elsewhere, which would be painful in conscious animals subjected to this procedure. In addition, instances of carotid arterial occlusion had no significant effect on the decrease in arterial blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…On the basis of hormonal data, there is little indication that U treatment was more stressful than LPNP or HPNP treatments at T3 (post-neck cut). Stunning within 5 s after throat cut would be expected to render the animals insensible to further pain and distress (Gibson et al 2009d). Shaw and Tume (1992) indicated that mechanical stunning elevates concentrations of circulating cathecolamines in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of hormonal data, there is little indication that U treatment was more stressful than LPNP or HPNP treatments at T3 (post-neck cut). Stunning within 5 s after throat cut would be expected to render the animals insensible to further pain and distress (Gibson et al 2009d). Shaw and Tume (1992) indicated that mechanical stunning elevates concentrations of circulating cathecolamines in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Cutting of the throat stimulates nociceotors located in the neck tissue that cause a barrage of impulses to travel to the brain ). Previous work reported by Gibson et al (2009aGibson et al ( , 2009bGibson et al ( , 2009cGibson et al ( , 2009d clearly illustrated the benefits of stunning in ameliorating the noxious stimuli associated with throat cut, on the basis of electroencephalogram (EEG) measurements in calves. However, interpretation of EEG changes for pain and stress evaluation should not be carried out without inferring to other concurrent measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have also been made to measure and study pain in humans using an electroencephalogram (EEG) which can reflect changes in brain electrical activity (Michels et al 2011), and there is an increasing number of papers that describe the use of EEG in animals (Diesch et al 2009;Gibson et al 2009;Johnson et al 2009). However, EEG also has its own specific methodological and interpretative limitations.…”
Section: Clinical Responses To Painmentioning
confidence: 99%
“…The third paper reported the impact of non-penetrative captive-bolt stunning on the features of the EEG, which were assessed quantitatively for the first time (Gibson et al 2009c) and indicated that the vast majority of animals were rendered insensible before data were able to be collected from about 3 seconds after stunning. The fourth paper assessed the extent to which applying a non-penetrative captive bolt stun 5 seconds after ventral-neck incision ameliorated the noxious sensory input caused by the incision (Gibson et al 2009d). This paper showed that the stun prevented the subsequent development of responses in the EEG to noxious sensory input in most of the animals.…”
Section: Calf Slaughter Studiesmentioning
confidence: 97%